Entropy Generation Minimisation of Imaging Concentrating Solar Collectors - Kalogirou, Soteris A. (My University, 2003)
There are three types of imaging concentrating solar collectors, the parabolic trough, the parabolic dish and the central receiver. The second law of thermodynamics is used to analyze the potential for entropy generation minimization of imaging concentrating solar collectors. It is shown that the amount of exergy (useful energy) delivered by solar concentrating collector systems is affected by heat transfer irreversibilities occurring between the sun and the collector, between the collector and ambient air and within the collector receiver (absorber). Analysis is performed and relations are derived in this paper by considering both, an isothermal and a non-isothermal collector which is a more realistic model particularly for the long parabolic trough collectors. Relations for the optimum operating conditions, in terms of the optimum collector outlet temperature for minimum heat transfer irreversibility or entropy generation minimization (or maximum exergy delivery), are derived. The importance of operating at the optimum delivery temperature is analyzed and optimum values of entropy generated are derived for the collector types considered.
Keywords: Solar collectors; Parabolic trough